KONSEP HISTORISITAS TEKS AL-QUR’AN: Telaah atas Pembacaan Kontemporer Muhammad Arkoun - Deden Mula Saputra; Latipah (STIQ al-Lathifiyyah Palembang, 2019)
Muhammad Arkoun is one of Muslim thinkers who offers a controversial theory of interpretation of the Qur'an. Arkoun argues for a project of criticism of Islamic reasoning, which supports the reexamining of the essence considered as well-established in the Islamic world, which for him is not in accordance with the true Islamic reasoning. Through deconstruction he criticizes discourse that is considered well-established in Islam and inseparable from its readers. One of them is about revelation, in which an important point of change is its historical plot that can been seen from the change of verbal revelation into a written corpus, or mushaf, which he considers as the point of problematization to restore the authenticity of the manuscripts and signifies a deviation in thought and interpretation. As a solution, Arkoun offers the concept of historicity in order to dismantle the discourse rooted for centuries.